Structure of Negative Symptoms in Schizophrenia: An Unresolved Issue - Russo, Manuela; Repisti, Selman; Blazhevska Stoilkovska, Biljana; Jerotic, Stefan; Ristic, Ivan; Mesevic Smajic, Eldina; Uka, Fitim; Arenliu, Aliriza; Bajraktarov, Stojan; Dzubur Kulenovic, Alma; Injac Stevovic, Lidija; Priebe, Stefan; et al. (Frontiers in Psychiatry, 2021)
Background. Negative symptoms are core features of schizophrenia and very challenging to be treated. Identification of their structure is crucial to provide a better treatment. Increasing evidence supports the superiority of a five-factor model (alogia, blunted affect, anhedonia, avolition and asociality as defined by the NMIH-MATRICS Consensus); however, previous data primarily used the Brief Negative Symptoms Scale (BNSS). Aims. This study (n=525 participants with schizophrenia) used the Clinical Assessment Interview for Negative Symptoms (CAINS) to explore the latent structure of negative symptoms, and test in a validation sample, theoretical and data-driven (from this study) models of negative symptoms. Methods. Exploratory factor analysis (EFA) was carried out to investigate the structure of negative symptoms based on the CAINS. Confirmatory factor analysis (CFA) tested in a validation sample four competing theoretical (one-, two-, five- and hierarchical factor) models and two EFA-derived models. Result. None of the theoretical models was confirmed with the CFA. A CAINS-rated model from EFA consisting of five-factors (expression, motivation for recreational activities, social activities, vocational, and close/intimate relationships) was an excellent fit to the data (comparative fix index=0.97, Ticker-Lewis index=0.96 and root mean square error of approximation=0.07). Conclusions. This study cannot support recent data on the superiority of the five-factor model defined by the NMIH-MATRICS consensus and suggests that an alternative model might be a better fit. More research to confirm the structure of negative symptoms in schizophrenia, and careful methodological consideration, should be warranted before a definitive model can put forward and shape diagnosis and treatment of schizophrenia.